Prevention of rushing attack in MANET using threshold-based approach. (8th May 2020) - Narayanan, S. Sankara; Murugaboopathi, G.
Mobile ad hoc networks are a collection of mobile nodes that works without the centralised infrastructure. Every mobile node not only acts as host, it also works as router to forward packets that are received from neighbour nodes. Mobile ad hoc networks are useful in military environments, automated battlefields, emergency, rescue operations, disaster recovery, educational, home and entertainment applications. Here data must be routed via intermediate nodes. Rushing attack is one of the network layer attacks in MANET. In this attack, when the attacker node receives the route request packet, it immediately forwards the route request packet to its neighbours without processing the packet. Threshold-based approach is used to detect rushing attack in MANET. Proposed method provides better packet delivery ratio and throughput in presence of rushing attacker. Simulation results show that our modified DSR protocol performs better compared to secure DSR algorithm.